2009
DOI: 10.1016/j.intcom.2008.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Older adults’ perceptions and experiences of online social support

Abstract: a b s t r a c tThis paper reports an investigation of older adults' needs and preferences concerning online social support. We focused our analysis on seven different aspects of online support: Self disclosure, Deep support, Light support, Community building, Information/Facts, Off topic, and Technical issues. For each aspect we were interested in how older adults perceive this aspect of support, what they think are the similarities and differences of this aspect of support in online settings vs offline settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 32 publications
3
67
0
6
Order By: Relevance
“…We're not seen as being able to be in a relationship, let alone have sex! (35) Members also reported difficulties in relation to people's reactions to their symptoms, which displayed a lack of understanding. This was particularly problematic for those members who were not displaying any overt or visible signs of disability, such as using a wheelchair:…”
Section: Sharing Difficulties Regarding Nmd Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…We're not seen as being able to be in a relationship, let alone have sex! (35) Members also reported difficulties in relation to people's reactions to their symptoms, which displayed a lack of understanding. This was particularly problematic for those members who were not displaying any overt or visible signs of disability, such as using a wheelchair:…”
Section: Sharing Difficulties Regarding Nmd Recognitionmentioning
confidence: 99%
“…This medium also offers anonymity for disclosing sensitive information [30] and allows people to choose whether to actively participate or 'lurk' and read online communications [31]. Potential disadvantages of online support groups include: 'flaming' or verbal harassment [32]; reading about other members' illness progression [33]; dealing with support group activity that is too high [27] or too low [34]; and variable quality of medical information [35]. However, analyses of online support group postings have revealed that the majority of messages are not erroneous or harmful [36,37] and analysis of message posts have been used to demonstrate the social support [34,38] and self-help [39,40] therapeutic functions of such groups.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on this phenomenon have been conducted recently, for instance comparing online and offline settings. For instance, Pfeil et al [6] highlight that older adults' perception of social support in online settings (such as online forums, chat rooms and social networking sites) is different comparing to their offline experiences; On one hand physical co-presence is very important for older adults for disclosing one's feelings to others and establishing a level of trust, which is a prerequisite for exchanging personal information in online settings. But on the other hand, the concern of being a burden -which is a reason for elderly' reluctance to talk about their problems -does not exist when disclosing information about oneself in online settings due to the anonymity and the fact that people do not have to face the other person directly when writing a message.…”
Section: Related Workmentioning
confidence: 99%
“…Through the TV one can broadcast programs meant for elderly, for example physiotherapeutic advice, rehabilitation programs and cooking tips. In addition Caring TV enables elderly people to communicate with health care professionals, who in real-time through a view phone give advice in areas concerning healthcare and well-being 6 .…”
Section: A Living Lab Approachmentioning
confidence: 99%
“…Braithwaite et al, 1999 ;Malik & coulson, 2008 ;Pfeil et al, 2009 ;Wright & Bell, 2003). L'amélioration de l'état émotionnel peut être le résultat d'une résolution de problème ; autrement dit, avoir trouvé une solution à la difficulté engendre une amélioration de l'état émotionnel.…”
Section: Une Communauté De Pairs Réactive Qui Partage Les Mêmes Pratiunclassified